(3HQfGeL GdhGO jGTis - (3CHh YHO Gddg eMeO Hf LGHQ Hf eMeO Hf GdbGSe Hf MSGfs; (3eMeO Hf LGHQ Hf eMeO Hf bGSe GdbjSj GdhGO jGTj GdJhfSj , TeS GdOjf CHh YHO Gddg,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi GdfYe CeG HYO aEf HYV CQHGH GdQhGjI PG GdTZa HgG hGdGgJeGe HgG hGdYfGjI s
(3BNQgG (B:s
(3eTjNg GdTjN Rjf GdOjf CMO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B68 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B146s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B45 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs